PENGETAHUAN DAN PENERAPAN PRINSIP HIGIENE SANITASI MAKANAN MINUMAN DI PANTI ASUHAN AISYIYAH AL WALIDATURRAHMAH - Putri Indah Permatasari; Vita Pramaningsih; Ratna Yuliawati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2024)
Food and beverage sanitation is a part of environmental health; controlling food and beverages is a primary function that must be carried out for food safety. Unhygienic drinks are just as dangerous as food; for human health, these beverages serve as sources of bacteria, poisoning, and other issues that can lead to death. The method used is descriptive in the form of a narrative about the depiction of knowledge and the application of food and beverage hygiene sanitation. The results of implementing the six principles of food and beverage hygiene and sanitation at the Aisyiyah Al Walidaturahmah Orphanage are as follows: for the variable of food ingredient selection, it meets the requirements with a score of 100%; for the variable of food ingredient storage, it also meets the requirements with a score of 100%; for the variable of food processing, it meets the requirements with a score of 92%; for the variable of storage of cooked food, it meets the requirements with a score of 100%; for food transportation, it meets the requirements with a score of 100%; and for food presentation, it meets the requirements with a score of 100%. The implementation of the six principles of food and beverage hygiene and sanitation has met health standards according to the Minister of Health Regulation Number 1096 of 2011.